Evaluation Of Production Cost Control Using Flexible Budget And Direct-Cost Variance In Restaurant Lamongan Sport Center: Evaluation Of Production Cost Control Using Flexible Budget And Direct-Cost Variance In Restaurant Lamongan Sport Center - Abdul Ghofur; Novianti Agustina; Rivatul Ridho Elvierayani (Jurnal Mantik, 2019)
Budgeting is a process of the preparatory phase required before the commencement of the preparation of the plan, the collection of necessary data and information, the division of the task of planning, the preparation of its own plan, the implementation and the plan until finally the stage of monitoring and evaluation of the results of implementing the plan. The hypothesis in this study is as follows: Suspected Cost Control Production using Efficient and Effective Flexible budget used in LA Restaurant. Suspected Cost Control Production using Direct Cost-Efficient and Effective Varian used at LA Restaurant. Suspected Cost Control Production using Flexible Budget and Direct-Cost Efficient and Effective Variant used in LA Restaurant. The results showed: The cost of raw materials "LA Restaurant" in 2012 until 2016 is under control. The direct labor cost of "LA Restaurant" in 2012 until 2016 is under control. The factory overhead cost of "LA Restaurant" in 2012 until 2016 is uncontrollable. The deviation is Rp. 1.237.287.435,00 (8.68%). The difference between the cost of raw materials and the difference indirect labor costs is advantageous while the difference in overhead costs is profitable